Predictors of NIV Treatment in Patients with COPD Exacerbation Complicated by Respiratory Acidaemia. (2nd September 2020) - Echevarria, Carlos; Steer, John; Hartley, Tom; Lane, Nicholas; Bourke, Stephen C.
Abstract: Non-invasive ventilation (NIV) treatment decisions are poorly understood for patients with COPD exacerbation complicated by acute hypercapnic respiratory failure and respiratory acidaemia (ECOPD-RA). We identified 420 NIV-eligible patients from the DECAF study cohorts admitted with an ECOPD-RA. Using bivariate and multivariate analyses, we examined which indices were associated with clinicians' decisions to start NIV, including whether the presence of pneumonia was a deterrent. Admitting hospital, admission from institutional care, partial pressure of oxygen, cerebrovascular disease, pH, systolic blood pressure and white cell count were all associated with the provision of NIV. Of these indices, only pH was also a predictor of inpatient death. Those not treated with NIV included those with milder acidaemia and higher (and sometimes excessive) oxygen levels, and a frailer population with higher Extended Medical Research Council Dyspnoea scores, presumably deemed not suitable for NIV. Pneumonia was not associated with NIV treatment; 34 of 111 (30.6%) NIV-untreated patients had pneumonia, whilst 107 of 309 (34.6%) NIV-treated patients had pneumonia ( p  = 0.483). In our study, one in four NIV-eligible patients were not treated with NIV. Clinicians' NIV treatment decisions are not based on those indices most strongly associated with mortality risk. One of the strongest predictors of whether a patient received a life-saving treatment is which hospital they attended. Further research is required to aid in the risk stratification of this patient group which may help standardise and improve care.